Aquatic Weeds: Crested Floating Heart (Nymphoides cristata) - Leif N. Willey; Kenneth A. Langeland (EDIS)
Crested floating heart is a native of Asia but was introduced to North America through the aquatic plant nursery trade and marketed as ‘snowflake.’ In the United States, crested floating heart escaped from cultivation and became established in Florida water bodies. Learn how to identify and manage this aquatic weed in this 5-page fact sheet written by Leif N. Willey and Kenneth A. Langeland and published by the UF Department of Agronomy, April 2011.